Exclusive breastfeeding and its relevance to infant teething - G. A. Chukwu; C. Ogbonna; M. F. Gyang; S. N. Okolo (Nigerian Dental Journal)
Objective: To determine the relevance of exclusive breast-feeding practice, in the development of healthy oral tissue among teething infants.